Modification of Titanium Dioxide Nanoparticles with 3-(Trimethoxysilyl)propyl Methacrylate Silane Coupling Agent. (28th October 2020) - Nguyen, Thuy-Chinh; Nguyen, Tien-Dung; Vu, Duc-Toan; Dinh, Duc-Phuong; Nguyen, Anh-Hiep; Ly, Thi-Ngoc-Lien; Dao, Phi-Hung; Nguyen, Thi-Len; Bach, Long-Giang; Thai, Hoang
Abstract : This paper presents some characteristics, properties, and morphology of TiO2 nanoparticles (nano-TiO2 ) modified with various contents of 3-(trimethoxysilyl)propyl methacrylate (TMSPM) coupling agent. The treatment process was carried out in ethanol solvent at 50 o C using ammonia as a catalyst for hydrolysis reaction of silane to silanol. Infrared spectroscopy, thermogravimetric analysis, transmission electron microscopy, field emission scanning electron microscopy, dynamic light scattering, ultraviolet-visible spectroscopy, and X-ray diffraction methods were used for determination of the characteristics, properties of nano-TiO2 before and after treatment. In addition, the contact angle and grafting efficiency of TMSPM on the surface of TiO2 nanoparticles was also evaluated. The obtained results confirmed that TMSPM was grafted to the TiO2 nanoparticles, the agglomeration of nano-TiO2 was decreased, and surface of TiO2 nanoparticles became hydrophobic after modification by TMSPM.